2011
DOI: 10.1016/j.rbmo.2011.02.015
|View full text |Cite|
|
Sign up to set email alerts
|

A single nucleotide polymorphism in BMP15 is associated with high response to ovarian stimulation

Abstract: There is substantial variability in ovarian response to exogenous gonadotrophins in women undergoing ovarian stimulation for IVF. Genetic variation in signalling pathways of the ovary may influence ovarian stimulation outcome. One previous study showed an association between single nucleotide polymorphisms (SNP) in the gene for bone morphogenetic protein 15 (BMP15) and ovarian hyperstimulation syndrome (OHSS). This article presents a retrospective case-controlled genetic-association study designed to test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
(47 reference statements)
3
36
0
1
Order By: Relevance
“…A study of 398 polycystic ovary syndrome (PCOS) women showed that, although the c.-9C>G variant was not related to disease pathogenesis, it might have been associated with specific clinical features, such as infertility (Gónzalez et al, 2008). Additionally, the c.-9C/G alleles have been related to differential ovarian response to recombinant FSH (rFSH) during assisted reproduction techniques, as the G allele has been linked to high responders Hanevik et al, 2011;Morón et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 398 polycystic ovary syndrome (PCOS) women showed that, although the c.-9C>G variant was not related to disease pathogenesis, it might have been associated with specific clinical features, such as infertility (Gónzalez et al, 2008). Additionally, the c.-9C/G alleles have been related to differential ovarian response to recombinant FSH (rFSH) during assisted reproduction techniques, as the G allele has been linked to high responders Hanevik et al, 2011;Morón et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while mutations in BMPR1B were observed in MODZT, they were only marginally associated with increased twinning (Luong et al 2011). Similar to the increased responsiveness to gonadotrophins observed in sheep heterozygous for a BMP15 mutation or homozygous for the BMPR1B mutation (McNatty et al 2006a), mutations in the human population in BMP15 have also been linked weakly to a higher response to FSH (Moron et al 2006, Hanevik et al 2011. In addition, the expression patterns for BMP15 and GDF9, as well as their receptors, are similar between sheep and humans .…”
Section: Mechanisms Of Action Of Gdf9 and Bmp15 And The Involvement Omentioning
confidence: 90%
“…This mutation in BMP15 is a rare example of X-linked human disease only in females who inherited the variant from an apparently unaffected father. Other variations and mutations in BMP15 have been recently reported in all cases associated with POF or ovarian hyperstimulation syndrome [Cordts et al, 2011;Hanevik et al, 2011]. It would be of interest to identify other mutations in BMP15 associated with 46,XX ovarian dysgenesis, to understand the mechanism of BM15 action in the development of human gonad.…”
Section: Gene Mutations Associated With Nonsyndromic 46xx Ovarian Dymentioning
confidence: 98%